Rancang Bangun Aplikasi Laporan Keuangan Yayasan NHR Berdasarkan SAK EP dan ISAK 335 - Mustofa Haqmaliah; Hera Khairunnisa; Umi Widyastuti (LPPM Universitas Negeri Jakarta, 2026)
This study aims to design and build a local web-based application that prepares the financial statements of Nur Hidayah Rusmaniah Foundation, an Islamic education foundation managing three units whose finances were previously recorded manually without a standardized accounting cycle. The application applies SAK EP for recognition and measurement and ISAK 335 for the presentation of five financial statement components. Development followed the Modified Waterfall with Prototyping method, combined with the ADDIE model to produce a guidance module for a treasurer without an accounting background. Data were collected through in-depth interviews, document analysis, and literature study. Testing consisted of batch-based dummy testing with historical transactions, Black Box Testing, and a user understanding test. The application generated all five statements required by ISAK 335 with results identical to manual reconstruction, passed every functional scenario, and the revised module enabled the treasurer to begin operating the system independently.